2010
DOI: 10.1111/j.1600-0501.2010.01966.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertical augmentation with interpositional blocks of anorganic bovine bone vs. 7‐mm‐long implants in posterior mandibles: 1‐year results of a randomized clinical trial

Abstract: When residual bone height over the mandibular canal is between 7 and 8 mm, 7 mm short implants might be a preferable choice than vertical augmentation, reducing the chair time, expenses and morbidity. These 1-year preliminary results need to be confirmed by follow-up of at least 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 17 publications
1
76
0
3
Order By: Relevance
“…Similar high implant survival rates were also documented in other RCTs with the same study design as the present study, but a shorter follow-up. [5][6][7][8][10][11][12]17 Only 2 other published randomized studies reported results after a similar or longer follow-up period, that is 3 years 38 and 5 years. 39 The sample size of the present investigation, with 52 patients and 122 implants, is wider than other prospective studies, except for the study by Thoma and colleagues that was a multicenter study involving 4 centres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar high implant survival rates were also documented in other RCTs with the same study design as the present study, but a shorter follow-up. [5][6][7][8][10][11][12]17 Only 2 other published randomized studies reported results after a similar or longer follow-up period, that is 3 years 38 and 5 years. 39 The sample size of the present investigation, with 52 patients and 122 implants, is wider than other prospective studies, except for the study by Thoma and colleagues that was a multicenter study involving 4 centres.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Currently, there is no evidence of superiority of one technique over the other. High implant and prosthesis survival rates for both short implants (SIs) and standard length implants in association with sinus lift were reported in several medium-short term clinical studies [5][6][7][8][9][10][11] and systematic reviews. [12][13][14][15][16] In addition, no statistical differences were reported for marginal bone loss.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the fact that a block higher than 10 mm was placed, which resulted in a vertical increase higher than the indications suggested by previous studies. 5,16,17 This resulted in a decrease of blood supply to the grafted block, both directly from the underlying basal bone and indirectly from the coronally placed segment, which, in turn, was malperfused due to the extreme expansion, causing lingual periosteum tension.…”
Section: Discussionmentioning
confidence: 98%
“…7,8,9,17 . Clinical studies have also shown that short implants are preferred over long implants associated with extensive reconstructive procedures 7,9,10,18 . Higher implant failure and more complications have been reported for patients undergoing bone graft, Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they also reduce the morbidity, treatment time, costs and complications rates. 5,6,7,8,9,10 Initially, short implants had a standard diameter (3.75 mm), received no surface treatment, and present preponderant failures rates. 11,12,13 Recent studies have shown positive results for short implants 1,8,14,15,16 even for those shorter than 7 mm in length.…”
Section: Introductionmentioning
confidence: 99%